O pássaro imaginário para flauta solo de Silvia Berg: a construção da performance através da relação compositor/intérprete - Sara Lima da SIlveira Costa (2013)
The work O Pássaro Imaginário for solo flute was composed by Silvia Berg in 2007. When the piece was debuted, in 2009, the significant amount of information in the score came to light. It was perceived how important it would be to establish research that contributed to performance of the piece. Berg, composer and professor at USP made references to Uirapuru's warble, bird that is part of the Brazilian collective imaginary. This work proposes reporting the preparation process of the performance of the piece with the interaction between composer / performer. The first chapter portrays the composer's life and some influences received. The second chapter discusses the bird theme and we will investigate some other pieces where the flute was related to the bird warble and how the musical treatment was given by other composers. The third chapter contains the analyze of the piece through the concepts of Gold Section and, after, a new proposal of commented edition that came from the relationship between composers and performer.